Emerging technologies for prenatal diagnosis: The application of whole genome and RNA sequencing. (18th April 2022) - Liu, Pengfei; Vossaert, Liesbeth
Abstract: DNA sequencing technologies for clinical genetic testing have been rapidly evolving in recent years, and steadily become more important within the field of prenatal diagnostics. This review aims to give an overview of recent developments and to describe how they have the potential to fill the gaps of the currently clinically implemented methods for prenatal diagnosis of various genetic disorders. It has been shown for postnatal testing that whole genome sequencing provides a set of added benefits compared to exome sequencing, and it is to be expected that this will be the case for prenatal testing as well. RNA‐sequencing, already used postnatally, can provide valuable complementary data to DNA‐based testing, and aid in variant interpretation. While not ready for clinical implementation, emerging technologies such as long‐read and Hi‐C sequencing analyses might add to the toolbox for interpreting the expanding genetic data sets generated by genome‐wide sequencing. Lastly, we also discuss some more practical implications of introducing these emerging technologies, which generate larger and larger genomic data sets, in the prenatal field. Key points: What is already known about this topic? Many studies have been published on the use and utility of prenatal exome sequencing, which is gradually being implemented in the standard workflow for prenatal diagnosis. What does this review add? This review discusses the potential value of applying newer technologies to the field of prenatal genetic testing, including whole genome sequencing, RNA‐sequencing, and other emerging technologies such as long‐read genome sequencing and Hi‐C analysis. We also reflect on the considerations for data interpretation and reporting that come along with these new 'omics data and are particularly important for the prenatal field.